Efficacy of Osimertinib in NSCLC Harboring Uncommon EGFR L861Q and Concurrent Mutations: Case Report and Literature Review - Lin, Ruiting; Chen, Ruilian; Chen, Zhiqiang; Hu, Leihao; Guo, Wei; Zhang, Zexin; Lin, Lizhu; Chen, Hanrui (Frontiers in Oncology, 2021)
The efficacy of first-and second-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in NSCLC patients with the EGFR L861Q mutation has been studied previously. However, there is little evidence on the efficacy of osimertinib in NSCLC patients with uncommon mutations. Here, we report the case of a 68-year-old man with advanced NSCLC with concurrent EGFR L861Q mutation as well as TP53 and RB1 mutations. The patient was treated with osimertinib as first-line therapy and achieved a remarkable progression-free survival of 15 months. His symptoms were significantly alleviated and the dose was well tolerated. The findings of the present study indicate that osimertinib might be a good treatment option for NSCLC patients with the L861Q mutation.